Safety Profile and Effects of Pulsed Methylprednisolone on Vital Signs in Thyroid Eye Disease - Kai-Ling Yong; Chiaw Ling Chng; Hla Myint Htoon; Lee Hooi Lim; Lay Leng Seah (International Journal of Endocrinology)
Objective. To analyze changes in vital signs (heart rate (HR), systolic (SBP), and diastolic blood pressure (DBP)) during and after intravenous methylprednisolone (IVMP) and any other adverse effects. Methods. Retrospective review of charts of patients who received IVMP as treatment regime for thyroid eye disease. All subjects had vital signs charted during and after infusions. Results. This study included 38 subjects and a total of 242 infusions administered. IVMP resulted in a small but significant percentage drop in mean SBP at 30 min (p<0.001) and 60 min (p=0.03) but no difference at 90 min. There was also small but significant percentage drop in mean DBP and HR (DBP: p<0.001 for 30 min, p=0.001 for 60 min, and p=0.02 for 90 min and HR: p<0.001 for 30 min, 60 min, and 90 min). There were no cumulative effects on change of blood pressure or HR. There were 6 episodes of bradycardia (2.5%) and 12 episodes of moderate to severe hypertension (5%). No significant cardiovascular or hepatic toxicity was found. Conclusion. IVMP is relatively safe and efficacious. IVMP demonstrated mild and noncumulative effects on vital signs. Severe hypertension may occur in susceptible individuals such as those with underlying hypertension and uncontrolled thyroid dysfunction, whereas bradycardia may be more likely in those on beta-blockers.